Raman spectra simulation of antiplatelet drug-platelet interaction using DFT - Anna Kundalevich; Anastasia Kapitunova; Kirill Berezin; Andrey Zyubin; Ekaterina Moiseeva; Vladimir Rafalskiy; Ilia Samusev (Scientific Reports, 2024)
Abstract The paper reflects the results of molecular docking and mathematical DFT simulation for antiplatelet drugs and the target platelet receptor/ferment interaction in the limited area. The results of Raman spectra simulation are implemented and obtained from the interaction of the clopidogrel metabolite of the P2Y12 receptor. The interaction of aspirin with the COX-1 enzyme was also investigated. As a result, theoretical Raman spectra of the drug-receptor area were obtained. The theoretical data were compared with the experimental SERS results. The characteristic bands corresponding to metabolite/ferment and antiplatelet drug vibrations were clarified. The prospects of obtaining results for pathologies based on platelet conformations during cardiovascular diseases have been demonstrated.